2017
DOI: 10.3389/fpsyg.2017.00854
|View full text |Cite
|
Sign up to set email alerts
|

How Do Soccer Players Adjust Their Activity in Team Coordination? An Enactive Phenomenological Analysis

Abstract: This study examined how individual team members adjust their activity to the needs for collective behavior. To do so, we used an enactive phenomenological approach and explored how soccer players' lived experiences were linked to the active regulation of team coordination during eight offensive transition situations. These situations were defined by the shift from defensive to offensive play following a change in ball possession. We collected phenomenological data, which were processed in four steps. First, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 42 publications
0
35
0
2
Order By: Relevance
“…Numerous recent qualitative studies have demonstrated the fruitfulness of this method for studying the dynamic of experience in the actor (e.g. [ 50 – 52 ]) and for studying emotion and stress [ 32 34 ]. The interview was very directive so as to provoke the re-emergence of elements of past experience when the participant was confronted with his own video recording.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous recent qualitative studies have demonstrated the fruitfulness of this method for studying the dynamic of experience in the actor (e.g. [ 50 – 52 ]) and for studying emotion and stress [ 32 34 ]. The interview was very directive so as to provoke the re-emergence of elements of past experience when the participant was confronted with his own video recording.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, access to pre-reflexive consciousness provides a disclosure of the world as meaningfully experienced by the agent. Furthermore, within the sports psychology literature, the course-of-action framework has already been used to gain insight into performance in many sports like trampoline and acrobatics (Hauw and Durand, 2004, 2008), skydiving (Mohamed et al, 2015), table tennis (Sève et al, 2005), orienteering (Mottet et al, 2016), rowing (Sève et al, 2013), soccer (Villemain and Hauw, 2014; Gesbert et al, 2017), and trail running (Antonini Philippe et al, 2016; Hauw et al, 2017; Rochat et al, 2017). All these studies analyzed embedded activity through activity analysis and were able to provide practical recommendations for training, education, and competition (e.g., Hauw, 2017, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…19, no 5, 2018, SPeCIaL ISSue (SCIenCe In SoCCeR and futSaL) humanmovement.pl different playing positions constantly interact with each other, e.g. defenders with the opposing forwards, midfielders with the opposing defenders, or forwards with the opposing midfielders [10,11]. From this interaction, players with a similar technical status, but with higher ASr, regardless of the playing position, could have an advantage over an opponent with lower ASr and similar MAS [1,4].…”
Section: Human Movement 66mentioning
confidence: 99%